2022
DOI: 10.3390/vaccines10101652
|View full text |Cite
|
Sign up to set email alerts
|

Cross-National Vaccine Concerns and Predictors of Vaccine Hesitancy in Not-Fully Vaccinated Individuals: Findings from USA, Canada, Sweden, and Italy

Abstract: Vaccine hesitancy is a key contributor to reduced COVID-19 vaccine uptake and remains a threat to COVID-19 mitigation strategies as many countries are rolling out the campaign for booster shots. The goal of our study is to identify and compare the top vaccine concerns in four countries: Canada, Italy, Sweden, and the USA and how these concerns relate to vaccine hesitancy. While most individuals in these countries are now vaccinated, we expect our results to be helpful in guiding vaccination efforts for additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Research has shown that a significant proportion of parents have concerns about the safety and effectiveness of vaccines [ 19 ], with some still believing that vaccines can cause autism. Even in developed countries, research has found that vaccine hesitancy remains a concern in Canada, despite high levels of vaccine acceptance [ 20 ]. In a study conducted in 2010 by Chang et al, the rate of people agreeing that vaccines cause autism was higher among hesitant parents (p < 0.001) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that a significant proportion of parents have concerns about the safety and effectiveness of vaccines [ 19 ], with some still believing that vaccines can cause autism. Even in developed countries, research has found that vaccine hesitancy remains a concern in Canada, despite high levels of vaccine acceptance [ 20 ]. In a study conducted in 2010 by Chang et al, the rate of people agreeing that vaccines cause autism was higher among hesitant parents (p < 0.001) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, as with any attitudes, vaccine hesitancy can change over time depending on the current circumstances (e.g., the presence of a pathogen within community). Third, our analysis focused on sociodemographic characteristics, though other factors may significantly affect vaccine hesitancy [36][37][38].…”
Section: Discussionmentioning
confidence: 99%